Green Chemistry in Pharmaceutical Manufacturing and Green Analytical Chemistry: Sustainable Pharmaceutical Development (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Artificial Intelligence (AI) is transforming pharmaceutical research by making drug discovery and development faster, more accurate, and environmentally sustainable. At the same time, Green Chemistry focuses on designing chemical processes that reduce the use of hazardous substances, minimize waste, conserve energy, and promote the use of renewable resources. The integration of AI with Green Chemistry has emerged as a powerful strategy for developing safer medicines while reducing the environmental impact of pharmaceutical manufacturing. AI technologies, including machine learning, deep learning, and predictive modeling, enable researchers to identify promising drug candidates, predict molecular properties, optimize chemical reactions, and reduce the need for repeated laboratory experiments. These capabilities significantly shorten development time, lower research costs, and improve the success rate of drug discovery. When combined with Green Chemistry principles, AI also helps in selecting eco-friendly solvents, designing energy-efficient synthetic pathways, minimizing toxic by-products, and improving resource utilization. This integrated approach supports sustainable pharmaceutical manufacturing by reducing chemical waste, lowering carbon emissions, and enhancing process efficiency without compromising drug quality or safety. Furthermore, AI-driven green methods contribute to regulatory compliance and promote responsible innovation in the pharmaceutical industry. Despite challenges such as data quality, computational requirements, and model validation, continuous advancements in artificial intelligence are expanding its role in sustainable drug development. In conclusion, the combination of Artificial Intelligence and Green Chemistry represents a significant advancement in modern pharmaceutical science. It offers an innovative pathway to accelerate drug discovery, improve manufacturing efficiency, reduce environmental impact, and ensure the development of safer, high-quality medicines for future healthcare needs.
Keywords: Artificial Intelligence; Green Chemistry; Drug Discovery; Sustainable Manufacturing; Pharmaceuticals